Schutz religiöser Gefühle im freiheitlichen Verfassungsstaat? - Rox, Barbara (Jus Ecclesiasticum, 2012)
How does the liberal constitutional state deal with heavy criticism of religion in public and with the impact of this? Barbara Rox gives a new assessment of the tensions between the law of church and state relations and the doctrine of fundamental rights as well as between national constitutional law and public international law. She focuses on the predominant theory of a conflict between freedom of opinion and freedom of religion and examines the viability of this theory.